PERMASALAHAN PERLINDUNGAN KONSUMEN - Wahon, Ernesta Uba; Robin, Lusia Meilania; Tukan , Christian Andryan Biola; Deze, Januarius Morison (Gapenas Publisher, 2025)
Consumer protection is a vital element in ensuring fairness in the relationship between businesses and consumers. In practice, consumers often face problems such as information asymmetry, unfair standard contracts, and weak bargaining positions in economic transactions. This article explores the fundamental principles of consumer protection—such as transparency, fairness, product reliability, and effective complaint mechanisms—along with the current challenges faced by consumers in Indonesia. Using a normative legal approach and theories of consumer law, this paper emphasizes the importance of state intervention in creating a fair and effective consumer protection system.